IMPLEMENTASI LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI GERAK DAN PENCERNAAN KELAS XI IPA SMAN 3 TANAH PUTIH - Efrinanda Afrianti; Arnentis Arnentis; Yustina Yustina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Absrtack: This study aims to improve students' learning outcomes through the application of Discovery Learning LKPD based on Gerakan material and digestive system class XI IPA SMAN 3 Tanah Putih. This research was conducted at SMAN 3 Tanah Putih Tanah Putih Subdistrict Rokan Hilir Regency in XI class of odd semester of academic year 2017/2018 in October - November 2017. This research is a Class Action Research (PTK) which was conducted in two cycles. The subjects of this study were students of class XI IPA SMAN 3 Tanah Putih academic year 2017/2018 consisting of 23 people consisting of 9 men and 14 women. The parameters observed are the absorption of learners, the learners' learning outcomes and the attitudes of learners. After the implementation of LKPD discovery learning-based absorption of learners in the first cycle of 89.65% good category increased in cycle II to 92.26% very good category. Students learn mastery in cycle I get an average of 86.95% good category increased in cycle II to 95.65% very good category. The attitude of learners in cycle I obtained an average of 85.38% good category increased in cycle II to 91.53% good category. From the results of the study can be concluded that the implementation of LKPD based learning discovery learning can improve the learning outcomes of students class XI IPA SMAN 3 Tanah Putih.Keywords: Implementation Worksheet Learners, Learning Results, Attitudes Learners